2020
DOI: 10.1136/bmjopen-2020-036904
|View full text |Cite
|
Sign up to set email alerts
|

Digital telemedicine interventions for patients with multimorbidity: a systematic review and meta-analysis

Abstract: ObjectiveTo determine the effectiveness of digital telemedicine interventions designed to improve outcomes in patients with multimorbidity.DesignSystematic review and meta-analysis of available literature.Data sourcesMEDLINE, EMBASE, The Cochrane Central Register of Controlled Trials, ClinicalTrials.gov, and the Database of Abstracts of Reviews of Effectiveness and hand searching. The search included articles from inception to 19 April 2019 without language restrictions. The search was updated on 7 June 2020 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 25 publications
1
25
0
2
Order By: Relevance
“…In response to the pandemic, the Centers for Medicare and Medicaid Services (CMS) and private insurers expanded coverage for both video and phone telehealth visits, and telemedicine utilization increased exponentially [3][4][5] and expanded into primary care [6,7]. While further study is needed to explore the challenges of telemedicine [8], initial studies have found that with certain patient populations and conditions, telemedicine is associated with a number of patient and clinician benefits, including reduced appointment wait times, costs, improved medication adherence and blood pressure control, and high rates of patient and clinician satisfaction [9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In response to the pandemic, the Centers for Medicare and Medicaid Services (CMS) and private insurers expanded coverage for both video and phone telehealth visits, and telemedicine utilization increased exponentially [3][4][5] and expanded into primary care [6,7]. While further study is needed to explore the challenges of telemedicine [8], initial studies have found that with certain patient populations and conditions, telemedicine is associated with a number of patient and clinician benefits, including reduced appointment wait times, costs, improved medication adherence and blood pressure control, and high rates of patient and clinician satisfaction [9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that targeted use of telemedicine and digital health is likely to realise the best outcomes. Digital telemedicine interventions have been shown, for example, to improve measures of disease control in chronic-illness patients, but have not demonstrated benefits for patients' overall health (Kraef et al, 2020). In addition, the form that telemedicine takes is important.…”
Section: Telemedicine In the Futurementioning
confidence: 99%
“…When including patients with comorbidities, they provided moderate evidence of improvements in measures of disease control, but little evidence and no demonstrated benefits on health status. Further research is needed with clear descriptions of conditions, interventions, and outcomes based on patients’ and healthcare providers’ preferences [ 13 ]. The continuous monitoring of vital signs may allow the detection of early signs of clinical worsening even of patients in a non-intensive care setting (including at home or within subacute facilities).…”
Section: Introductionmentioning
confidence: 99%